Prevalence of intestinal parasitic infections and associated factors among pregnant women attending antenatal care at Yirgalem General Hospital, Sidama, Ethiopia - Aregahegn Dona Buchala; Siyoum Tesfaw Mengistu; Azmach Dache Mue; Amelo Bolka Gujo (Elsevier, 2022)
Background: In poor countries like Ethiopia, the burden of intestinal parasitic infections (IPIs) is high. Thus, this study was aimed to assess the prevalence of IPIs and associated factors among pregnant women attending antenatal care clinics at Yirgalem General Hospital, Sidama, Ethiopia. Methods: A cross-sectional study was conducted among systematically selected 400 pregnant women. Trained data collectors administered the questionnaire. The stool samples were collected and analyzed. SPSS version-25 was used for data analysis. Descriptive statistics, bivariable and multivariable logistic regression analysis were done. Adjusted odds ratio (AOR) with 95% confidence interval (CI) was used to measure the presence and strength of association. A p-value ≤0.05 was considered to declare statistical significance. Results: The prevalence IPI was 35.8% (95% CI: 31.1, 40.5%). Increased odds of IPIs observed among pregnant women who lived in the rural area, ate unwashed fruits/vegetables, drank water from the unprotected source, drank untreated water, not washed hands by soap, and had a history of previous IPI. Conclusion: Prevalence of IPIs was high. Thus, strengthening health education on the appropriate handling of foods, keeping personal and environmental hygiene, and protecting the source of drinking is crucial. Further, therapeutic and prophylactic intervention according to the World Health Organization deworming protocol is also important to tackle this problem.